Surface texturing potential on carbide insert in reducing aluminium alloy adhesiveness during machining - Chia, Yun Qi; Mohd Nizar, Mhd Razali; Ahmad Shahir, Jamaludin; Ahmad Redza, Ahmad Mokhtar; Saiful Bahari, Hamzah; Mohd Shahril, Osman (Penerbit UMP, 2019)
Aluminum alloy is a widely used material which contributes greatly in numerous engineering applications. Aluminum alloy can be considered as having low strength and it is less likely to experience tooling difficulty. However, the complexity of machining aluminum alloy is related to its adhesive behavior, which capable to impede the machining operations where build-up-edge can be observed easily to occur. Since machining process generates a lot of energy due to friction and adhesive contact between tool and material, it is suggested to apply wet cutting method during machining of aluminum alloy to decrease the likeliness of aluminum alloy chip to adhere onto the tool surface. However, this method of machining is still having low effectiveness whereas the limitation of cutting fluid to enter the tool-chip sticking zone. Thus, the fabrication of textures on carbide insert rake surface is one of the predominant methods to enhance the sustainability of turning process with aluminum alloy workpiece. In this study, grinding process was utilized using Okamoto ACC52ST surface grinding machine to fabricate textures, where it is assumed that high effectiveness of lubricant can be retained and friction at tool-chip interface can be reduced. Turning process was conducted with the application of ROMI C420 lathe machine to investigate the adhesive behavior of aluminum alloy. It is observed that, the adhesive behavior of aluminum alloy was minimized with the application of textured carbide insert especially in wet cutting condition in general. Additionally, it can observed that, even at relatively high cutting speed and depth of cut, less adhesion behavior of aluminum alloy is obtained for textured carbide insert in wet cutting condition. This can be considered as a gain in productivity, whereas the adhesive behavior for non-textured carbide insert can only be reduced if only low cutting speed condition and wet cutting method are utilized.